Papel das espécies reativas de oxigênio no desenvolvimento da resposta inflamatória na doença do enxerto contra hospedeiro induzida em camundongos - Priscila Teles de Toledo Bernardes (2016)
ntroduction: Graft-versus-host disease (GVHD) is the greatest complication limiting the clinical utility of allogeneic hematopoietic stem cell transplantation (HSCT), in which lymphocytes of donors (graft) are activated in response to host antigen. This disease is associated with increased inflammatory response through the release of inflammatorymediators such as cytokines, chemokines and reactive oxygen species (ROS). Here, we evaluate the role of ROS in the GVHD pathogenesis. Methods: GVHD was induced by the transplant of 1x107 bone marrow cells + 3x107 splenocytes from C57BL/6 mice (GVHD group). The control group received isogenic cells from B6D2F1 mice. To assess the role ofROS in the pathogenesis of GVHD, mice subject to GVHD were treated with apocynin (APO group), an inhibitor of the intracellular translocation of cytosolic components of the NADPHoxidase complex, using 3mg/Kg every day. The levels of ROS were analyzed in spleen, bone marrow, liver and intestine following phases of development of clinical disease: onset of clinical disease (day 6) and mortality (day 13). The inflammatory response was assessed by analysis of oxidative stress (superoxide t dismutase, catalase and lipid peroxidation), the levels of cytokines and chemokines by ELISA, indirect quantification of macrophages by Nacetylglucosaminidase activity (NAG), histopathological parameters, recruitment, adhesion and accumulation of leukocytes by intravital microscopy or flow cytometry in the early mortality of GVHD. We also investigated the accumulation of inflammatory cells in lymphoidorgans by flow cytometry onset mortality. The survival and clinical score of disease were evaluated. Results: Levels of ROS were increased in target organs of GVHD mice and reduced in apocynin-treated mice at day 6 and spleen and bone marrow and at day 13 in the liver. We verified a reduction of TBARS, in levels of IFN-gamma, TNF-alpha, IL-17, CCL2,CCL3, CCL5, accumulation of macrophage associated a less histopathology parameters in liver and intestine of mice treated with apocynin. Mechanistically, pharmacological blockade of the NADPH-oxidase was associated with decreased rolling and adhesion of leukocytes to The mesenteric microcirculation, as assessed by intravital microscopy. Moreover, the experiments showed that apocynin-treatment reduced the CD4+, CD8+ cells and macrophage accumulation in organs. The pharmacological blockade of NADPH oxidase resulted inreduced mortality (70%) and less incidence and severity of clinical scores of GVHD. We also observed that the treatment with apocynin did not alter the beneficial effect of graft-versustumor Conclusion: Our study demonstrates that ROS plays an important role in mediating GVHD. We suggest that strategies aimed at blocking the ROS production should be evaluated further for their usefulness as an adjuvant treatment in patients undergoing bone marrow transplant.